2019
DOI: 10.1155/2019/2935498
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Puncture Sites of Portal Vein in TIPS with ePTFE-Covered Stents on Postoperative Long-Term Clinical Efficacy

Abstract: Purpose To evaluate the effect of puncture sites of the portal vein in transjugular intrahepatic portosystemic shunt (TIPS) on long-term clinical efficacy. Methods A retrospective review was performed, including consecutive 171 patients who underwent TIPS with ePTFE-covered stents. All patients were divided into 3 groups according to the puncture site of the portal vein: intrahepatic bifurcation of the portal vein (group A, n = 88), right branch of the portal vein (group B, n = 48), and left branch of the port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…First, patients in the SV group and SMV group were relatively small, limiting the ability to draw firm conclusions. Second, other outcomes such as shunt dysfunction and mortality were not assessed in our study, which were reported to have a correlation with different puncture site [9,10,13], though the results were controversial. Third, the reliability of identification of portal flow diversion may be confounded by different catheter position and different contrast dose, and standardized portography protocol should be generated.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…First, patients in the SV group and SMV group were relatively small, limiting the ability to draw firm conclusions. Second, other outcomes such as shunt dysfunction and mortality were not assessed in our study, which were reported to have a correlation with different puncture site [9,10,13], though the results were controversial. Third, the reliability of identification of portal flow diversion may be confounded by different catheter position and different contrast dose, and standardized portography protocol should be generated.…”
Section: Discussionmentioning
confidence: 88%
“…The association between stent diameter and overt HE has been well established [5,6], while the effect of stent position on the outcome has not been fully elucidated. An early randomized-controlled trial (RCT) and few observational studies suggested that puncture of the left branch of portal vein (PV) might decrease the risk of post-TIPS overt HE compared to the right branch [7][8][9][10][11][12][13], and the potential mechanism might be related to the unbalanced distribution of blood flow from splenic vein (SV) and superior mesenteric vein (SMV) in the intrahepatic portal system. However, this theory lacks of hemodynamic evidence and may not be applicable to all cirrhotic patients due to anatomic variation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we identified the shunting branch of the PV as being an independent risk factor for TIPS stent dysfunction. Several studies have shown that the rate of long-term patency of the left branch of the portal vein is significantly higher than that of the right branch (10,21,26). The main reasons for this effect are as follows: (1) the stent shunt has better plasticity and is less likely to produce pseudointimal hyperplasia and stenting stricture due to the straighter puncture trajectory between the middle hepatic vein and the left portal vein ( 27);…”
Section: Discussionmentioning
confidence: 99%
“…This is related to the right branch of the portal vein contains more poisons mainly received from the superior mesenteric vein[ 21 - 23 ]. It was reported that choosing the left branch of the portal vein as the puncture site during the placement of TIPS may decrease the incidence of HE significantly[ 24 , 25 ]. HE occurs more often in patients with a stent diameter of 10 mm than in those with smaller-diameter stents.…”
Section: Discussionmentioning
confidence: 99%